Spermidine, an intrinsic component of turnip yellow mosaic virus. - Cohen, S S (1981)
The major polyamine of turnip yellow mosaic virus has been identified as spermidine by gas chromatography and mass spectrometry of the trifluoroacetamido derivative. Very small amounts of putrescine and cadaverine, but not norspermidine, have been detected in the virus. The spermidine contents of numerous virus preparations were in the range 200-700 molecules per virion and were considerably in excess of those of spermine. The RNA and spermidine contents of small amounts of the virus were determined after serological precipitation in purified preparations and in the juice of infected plants. Under conditions of the precipitation or purification from juice by differential centrifugation, only small amounts of exogenous radioactive spermidine and spermine became bound to virus. Although adsorbed radioactive spermidine could be removed almost quantitatively by washing the virus in dilute buffers, only a small part of adsorbed spermine was removed by such treatment. However, greater than 95% of the newly attached spermine was separated from the virus without loss of the original spermidine by sedimentation in buffers containing 0.5 M NaCl or 0.06 M MgCl2. Crystallization of virus in 40% saturated MgSO4 or 7.5% heparin or dialysis did not decrease viral spermidine. Although the virus coat may adsorb small amounts of the polyamines reversibly, the virus is impermeable to exogenous spermidine and spermine and does not exchange or leak internal spermidine. The spermidine present in purified virus is associated with viral RNA at the time of packaging and formation of intact virions.